Analysis of Restaurant Sanitation Hygiene in The Working Area Of Sempaja Community Health Center, Samarinda City - Rahmatullah, Ilham; Apriyani, Apriyani; Lani, Maria Droste (Sean Institute, 2023)
Hygiene and sanitation greatly affect food safety so that food is not contaminated, while sanitation of sales places is carried out to control environmental conditions from the handling of raw materials to the distribution process. This study aims to analyse how trash cans, handwashing facilities, and the personal hygiene of food handlers work. This study used a qualitative method with a phenomenological approach and was carried out in a restaurant in the working area of the Sempaja Health Centre, Samarinda City. The method of data analysis involves collecting data, reducing data, presenting data, and verifying it. The results showed that of the four restaurants with trash cans, there were two that met the requirements, namely PM and WBS restaurants, and there were two restaurants that did not meet the requirements, namely ABS and C. requirements. Personal hygiene has not fully met the requirements for restaurant sanitation hygiene, and for the implementation of complete personal protective equipment, the four restaurants have not met the requirements. It is suggested that trash bins need to be provided with organic and inorganic containers that are closed and made of waterproof material lined with plastic bags for ABS and restaurant C restaurants, while for handwashing places it is necessary to provide liquid soap, running water, wipes, and tissues for the four houses. Food and sewerage must be a closed channel for restaurants ABS, C, and WBS. Personal hygiene requires the four restaurants to wear complete personal protective equipment such as aprons, head coverings, and masks, as well as short nails, and wear neat work clothes and clean.